2016
DOI: 10.1111/cobi.12800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of life‐history requirements on the distribution of a threatened reptile

Abstract: Survival and reproduction are the two primary life-history traits essential for species' persistence; however, the environmental conditions that support each of these traits may not be the same. Despite this, reproductive requirements are seldom considered when estimating species' potential distributions. We sought to examine potentially limiting environmental factors influencing the distribution of an oviparous reptile of conservation concern with respect to the species' survival and reproduction and to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…First, the zone of high forest cover in eastern Texas could simply represent a climatic zone that delineates the range of the species. Forest cover in eastern Texas is associated with increased precipitation (Griffith et al 2007), and it is expected that an obligate inhabitant of aquatic habitats would fare optimally under such conditions (Thompson et al 2016). High precipitation and flooding in watersheds of this region increase potential for permanence and connectivity of the alligator snapping turtle's preferred habitat (Griffith et al 2007), which would in turn increase its dispersal potential throughout aquatic habitats of these watersheds.…”
Section: Discussionmentioning
confidence: 99%
“…First, the zone of high forest cover in eastern Texas could simply represent a climatic zone that delineates the range of the species. Forest cover in eastern Texas is associated with increased precipitation (Griffith et al 2007), and it is expected that an obligate inhabitant of aquatic habitats would fare optimally under such conditions (Thompson et al 2016). High precipitation and flooding in watersheds of this region increase potential for permanence and connectivity of the alligator snapping turtle's preferred habitat (Griffith et al 2007), which would in turn increase its dispersal potential throughout aquatic habitats of these watersheds.…”
Section: Discussionmentioning
confidence: 99%
“…Additional variables that could be important in describing suitable habitat for Alligator Snapping Turtles that were not incorporated into the model include food availability and flow rate (Shipman 1993, Riedle et al 2009), water depth (Howey and Dinkelacker 2009, Riedle et al 2006, Townsend 2016), flood frequency and dispersal barriers (Riedle et al 2008a), and climate (Thompson et al 2017). Many of these variables have been included in large-scale niche models spanning the current distribution of Alligator Snapping Turtles in the United States (Thompson et al 2017, USGS 2017). All of these factors should be considered alongside the output of the HSI model before a site is deemed suitable for reintroductions.…”
Section: Discussionmentioning
confidence: 99%
“…Sites that were resurveyed confirmed that occupancy and demography of M. temminckii within these areas remained generally stable over the past 2 decades. Higher CPUE than in Oklahoma and Louisiana may attest to benefits of more stringent protection of the species in Texas (Texas Register 1987). D.…”
Section: Conservation Implicationsmentioning
confidence: 99%